Evaluation of the Implementation of Minimum Service Standards for Hypertension Program - Handiny, Febry; Asyari, Dian Paramitha; Novera, Milya; Oktaviani, Silvy (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
The prevalence of hypertension in Indonesia in the 2018 National Riskesdas was 34.11%. Minimum Service Standards for hypertension: Every patient with hypertension receives health services according to standards. Achievement of Hypertension at Andalas Public Health Center for the last two years is 30.21% in 2021 and 14% in 2022. This study aims to determine the process of implementing the Minimum Service Standards for the Hypertension program at the Andalas Public Health Center. This study is a Descriptive qualitative research method by conducting semi-structured interviews with ten informants. The research was conducted at Andalas Public Health Center from March to August. The data collected were the results of interviews using an interview guide, document review, and observation. Data analysis used source triangulation and method triangulation. The results were that the officers involved and hypertensive patients in implementing Minimum Service Standards Hypertension were by the standards. Facilities and infrastructure are sufficient, but adding blood pressure monitors and Communication, Information, and Education media in leaflets is still necessary. Existing health workers already know the process of implementing hypertension following standards. The implementation has been going well, but there are still obstacles in the form of difficulty monitoring hypertensive patients in the Andalas Public Health Center working area and a lack of public awareness of routine treatment every month.